2023
DOI: 10.3389/fendo.2023.1188969
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the effects of denosumab and romosozumab on bone mineral density and turnover markers in patients with osteoporosis

Abstract: PurposeTo assess the alterations in bone mineral density and bone turnover marker concentrations following the administration of denosumab and romosozumab therapies in patients with osteoporosis.MethodsPubMed was searched for studies published until January 28, 2023, that investigated the clinical efficacy and bone turnover marker changes of denosumab and romosozumab in the treatment of osteoporosis, with a minimum follow-up of 3 months in each study. Studies were screened, and data on changes in bone mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Denosumab and Romosozumab, other osteoanabolic agents, have shown an even greater BMD improvement at the lumbar spine and hip through blockade of the inhibitory effects of sclerostin, which results in an increase in bone formation and decrease in bone resorption [33,34]. Multiple studies have demonstrated superiority of Romosozumab compared to Denosumab for improving BMD at twelve months [35]. However, compared to Denosumab, treatment with Romosozumab is limited to 12 months and cessation is associated with rapid loss of its effects on BMD [36,37].…”
Section: Pre-procedural Optimizationmentioning
confidence: 99%
“…Denosumab and Romosozumab, other osteoanabolic agents, have shown an even greater BMD improvement at the lumbar spine and hip through blockade of the inhibitory effects of sclerostin, which results in an increase in bone formation and decrease in bone resorption [33,34]. Multiple studies have demonstrated superiority of Romosozumab compared to Denosumab for improving BMD at twelve months [35]. However, compared to Denosumab, treatment with Romosozumab is limited to 12 months and cessation is associated with rapid loss of its effects on BMD [36,37].…”
Section: Pre-procedural Optimizationmentioning
confidence: 99%